THE PLOT ANALYSIS OF MOVIE â€œTHE LAKE HOUSEâ€ DIRECTED BY ALEJANDRO AGRESTI - Bayu Adhi, Sukmono (Aksara Public, 2018)
The purpose of this study was to find out about the plot that exist in movie â€œThe Lake Houseâ€ where the writer used a qualitative method. The writer was interested in analyzing this movie because the movie contained some advantages especially for those who want to use the movie as a medium of learning. The first advantage was that the story in this movie was very unique with the forward and backward plot. The second, this moviecontains the high value of literary arts. And the third, thatthe dialogue in this movie was not too fast, so that it was very useful to make the language learners easy to learn English. The results showed that the plot of this movieconsisted of six parts. They were preliminary exposition, starting point, rising action, climax, falling action, and ending.Understanding the plot was very important for the audience to make the story easier to be understood.